1959
DOI: 10.5962/bhl.title.85585
|View full text |Cite
|
Sign up to set email alerts
|

A guide to the literature on certain effects of light on fungi : reproduction, morphology, pigmentation, and photoropic phenomena /

Abstract: Achlya recurva. Cultures were placed in darkness and in diffuse daylight on top of a laboratory table at approximately the same temperature. They were examined after 72 hours. Dark cultures were then left in daylight for an additional 72 hours. Light was necessary for the germination of zygotes. (Ziegler, A. W. , 1948). Albugo occidentalis. Hanging-drop slides of conidia were arranged in a chamber at 12°C so that light from a 3-cell flashlight fell on them, while others were placed in the dark. Results after 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

1963
1963
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 96 publications
(109 reference statements)
0
15
0
1
Order By: Relevance
“…There are several reports (Marsh, Taylor, and Bassler 1959) that light influences the types of spores produced by F. solani. In this study also, light affected the type but not the number of spores produced.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports (Marsh, Taylor, and Bassler 1959) that light influences the types of spores produced by F. solani. In this study also, light affected the type but not the number of spores produced.…”
Section: Discussionmentioning
confidence: 99%
“…For example, light is essential for some species but not for others2, 1,5,6,7,8,10,12,13). In the isolates of Pyricularia studied, light was essential for the consistent production of perithecia.…”
Section: Effect Of Media On Perithecial Productionmentioning
confidence: 98%
“…This may result indirectly from light-induced increase in the production of black mycelium. Light has been shown to affect morphology and reproduction in many fungal species from diverse genera (Marsh et al, 1959). Studies have indicated a light requirement for pseudothecial and ascospore formation by Mycosphaerella ligulicola, the ray-blight pathogen of chrysanthemum (McCoy et al, 1972).…”
Section: R Kennedy Et Al 304mentioning
confidence: 99%